2022
DOI: 10.3389/fnut.2022.1009807
|View full text |Cite
|
Sign up to set email alerts
|

Crocin: Functional characteristics, extraction, food applications and efficacy against brain related disorders

Abstract: Crocin is a bioactive compound that naturally occurs in some medicinal plants, especially saffron and gardenia fruit. Different conventional and novel methods are used for its extraction. Due to some control conditions, recent methods such as ultrasonic extraction, supercritical fluid extraction, enzyme-associated extraction, microwave extraction, and pulsed electric field extraction are widely used because these methods give more yield and efficiency. Crocin is incorporated into different food products to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…It would be difficult to establish specific data on intake and recommended daily intake of polyphenolic compounds, also without omitting important insoluble polyphenols [ 35 , 64 ]. Currently, it is believed that polyphenolic compounds should be consumed together with five daily meals, and such intake is estimated at 0.5–1 g. According to the collected data, the most ingested polyphenols were flavonoids, and their consumption in Western countries varies between 50–800 mg.…”
Section: Polyphenolic Compounds As a Considerable Plant Component Of ...mentioning
confidence: 99%
“…It would be difficult to establish specific data on intake and recommended daily intake of polyphenolic compounds, also without omitting important insoluble polyphenols [ 35 , 64 ]. Currently, it is believed that polyphenolic compounds should be consumed together with five daily meals, and such intake is estimated at 0.5–1 g. According to the collected data, the most ingested polyphenols were flavonoids, and their consumption in Western countries varies between 50–800 mg.…”
Section: Polyphenolic Compounds As a Considerable Plant Component Of ...mentioning
confidence: 99%
“…The fruit of G. jasminoides , with the Chinese name ‘ Zhi Zi ’ after drying treatment, has been used as a traditional Chinese medicine for thousands of years. Many biological properties in vitro and in vivo have been discovered by modern scientific evaluation in recent decades, including antidiabetic (Wang et al ., 2019), anti‐inflammatory (Wang et al ., 2020), anti‐depression (Tao et al ., 2014) and antioxidant properties (Ali et al ., 2022). Additionally, it has been reported that the fruit of G. jasminoides improved sleeping quality (Tian et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It belongs to the plant family and derives from the Greek word “Kera.” These fruits have keratomorphic shapes which are the Latin word siliqua that refers to the pods' hardness and shape (Papaefstathiou et al, 2018). The carob tree ( C. siliqua L.) is a native tree in the region of Mediterranean, and there occupies great importance on account of economic and environmental conditions (Ali, Kousar, et al, 2022; Benković et al, 2016). Carob fruit has a tough‐to‐crack pod that is elongated, flat, arced or straight, and thick sutures.…”
Section: Introductionmentioning
confidence: 99%
“…The carob tree (C. siliqua L.) is a native tree in the region of Mediterranean, and there occupies great importance on account of economic and environmental conditions (Ali, Kousar, et al, 2022;Benković et al, 2016). Carob fruit has a tough-to-crack pod that is…”
mentioning
confidence: 99%